Phytoremediation-biorefinery tandem for effective clean-up of metal contaminated soil and biomass valorisation. Issue 11 (2nd November 2017) - Sotenko, Maria; Coles, Stuart; Barker, Guy; Song, Lijiang; Jiang, Ying; Longhurst, Philip; Romanova, Tamara; Shuvaeva, Olga; Kirwan, Kerry
ABSTRACT: During the last few decades, phytoremediation process has attracted much attention because of the growing concerns about the deteriorating quality of soil caused by anthropogenic activities. Here, a tandem phytoremediation/biorefinery process was proposed as a way to turn phytoremediation into a viable commercial method by producing valuable chemicals in addition to cleaned soil. Two agricultural plants ( Sinapis alba and Helianthus annuus ) were grown in moderately contaminated soil with ca. 100 ppm of Ni and further degraded by a fungal lignin degrader— Phanerochaete chrysosporium . Several parameters have been studied, including the viability of plants, biomass yield, and their accumulating and remediating potentials. Further, downstream processing showed that up to 80% of Ni can be easily extracted from contaminated biomass by aqueous extraction at mild conditions. Finally, it was demonstrated that the growth of plants on the contaminated soil could be degraded by P. chrysosporium, and the effect of nickel and biomass pretreatment on the solid-state fermentation was studied. The proposed and studied methodology in this work could pave the way for successful commercialization of the phytoremediation process in the near future.